Visitors' identification of landmarks in the historic district of Banda Hilir, Melaka, Malaysia - Mirsa Hussain, Khairul Amin; Ujang, Norsidah (Elsevier, 2014)
Landmark is one of the key elements that shape the image and identity of historic cities. It is evident that new and unfit developments have diluted the dominance of landmarks in Banda Hilir, Melaka. This paper examines visitors’ identification of landmarks in Banda Hilir and its influence on the visitors’ imageability. The study adopted mental mapping technique to gather images regarded as landmarks and its corresponding characteristics. Results from the study indicate that visitors identified both buildings and open spaces as landmarks. Size, façade, color and scale influence their identifications. This study denotes the importance of landmarks in preserving the character of Bandar Hilir, despite the addition of new structures.